2019
DOI: 10.1177/0269881119882854
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of the dual orexin receptor antagonist ACT-541468 in elderly subjects: Exploration of pharmacokinetics, pharmacodynamics and tolerability following single-dose morning and repeated-dose evening administration

Abstract: Background: The dual orexin receptor antagonist ACT-541468 showed sedative pharmacodynamic effects during initial clinical testing in adult subjects. The present study explored pharmacokinetics, pharmacodynamics and tolerability in healthy elderly subjects. Methods: Double-blind, placebo-controlled, randomised, single-ascending dose study in 24 male/female elderly (65–80 years, 5, 15 and 25 mg in the morning, 6/2 active/placebo per group). Additionally, 10 subjects (8/2 active/placebo) received 25 mg for 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 51 publications
4
32
0
3
Order By: Relevance
“…In the present study, daridorexant was safe and well tolerated at the dose of 50 mg based on AE and other safety data, suggesting that daridorexant does not worsen the disease condition in patients with moderate COPD. Except for one AE of fatigue, none of the reported AEs was suggestive of next‐day residual effect of daridorexant, consistent with previous studies in healthy subjects (Muehlan, Boehler, et al., 2020; Muehlan et al., 2018, 2019; Muehlan, Zuiker, et al., 2020) and patients with insomnia (Dauvilliers et al., 2020; Zammit et al., 2020).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, daridorexant was safe and well tolerated at the dose of 50 mg based on AE and other safety data, suggesting that daridorexant does not worsen the disease condition in patients with moderate COPD. Except for one AE of fatigue, none of the reported AEs was suggestive of next‐day residual effect of daridorexant, consistent with previous studies in healthy subjects (Muehlan, Boehler, et al., 2020; Muehlan et al., 2018, 2019; Muehlan, Zuiker, et al., 2020) and patients with insomnia (Dauvilliers et al., 2020; Zammit et al., 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Daridorexant and placebo were orally administered at night‐time for 5 consecutive days. The 5‐day exposure duration was considered sufficient, as steady state exposure of daridorexant and its metabolites is reached after 3 days without relevant accumulation, as previously determined in healthy subjects (Muehlan, Boehler, et al., 2020; Muehlan et al., 2019; Muehlan, Zuiker, et al., 2020). Both study periods were separated by a washout period lasting 1–2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the safety profile of daridorexant was similar to previous observations. 5,8,[11][12][13]20 Administration of daridorexant was well tolerated in all individuals and no safety concern related to the administration of daridorexant was raised.…”
Section: Discussionmentioning
confidence: 98%
“…PK results in control subjects in this study were within the range of variability observed in other studies, in which a single oral dose of 25 mg daridorexant was administered to a similarly aged population. 11 , 12 , 20 An apparent explanation for the outlier in group A could not be determined as nothing out of the ordinary in terms of demographic characteristics, medical history, and clinical laboratory variables was evident, whereas there was no concomitant intake of other drugs. The inherent variability of expression and function of CYP3A4, both intra‐ and interindividually, is considered a possible explanation.…”
Section: Discussionmentioning
confidence: 99%